Factors associated with utilization of insecticide treated nets among pregnant women in northern regions of Namibia - Mbago, Thomas (My University, 2014)
Background: Malaria causes an overwhelmingly large number of cases and deaths around the globe every year, with over 90% of deaths occurring in sub-Saharan Africa. Namibia is among the sub Saharan countries that have malaria as a major public health problem, affecting most pregnant women and children in the northern regions. Insecticide treated net (ITN) distribution has been expanded in the northern regions since 2005, yet there is low ITN utilization. The associated factors for low ITN utilization are not well established. Objective: This study aimed to determine factors affecting the utilization of ITN among pregnant women in northern regions of Namibia. Specific objectives were to: (1) describe coverage of ITNs among pregnant women in terms of possession; (2) describe the utilization rate of ITN among pregnant women in northern regions; and (3) determine the association between various factors and utilization of ITN among pregnant women. The first study outcome measure was utilization of ITN, defined as an individual pregnant woman who had used an ITN the night before the survey day. The second outcome measure was coverage of ITNs, defined as possession of at least one ITN in each household, irrespective of whether or not it was being used. Methods: A cross sectional study design was used, using secondary data from a nationally representative survey which collected data on malaria interventions in regions of Namibia. The original survey collected data from a representative sample of 3000 households from 120 primary sampling units (PSUs) in nine regions country wide, using a stratified sampling method of two stages. This study targeted pregnant women in four northern regions, namely; Kavango, Ohangwena, Oshana and Omusati, in both rural and urban areas; who participated in the 2009 Namibia Malaria Indicator Survey (NMIS) from 4 April to 10 June 2009. A total of 83 pregnant women were included in the analysis out of 194 pregnant women who were interviewed during the 2009 survey. In the descriptive analyses, we described the demographic characteristics of pregnant women. In the analytic analyses, univariable and multivariable analysis (logistic regression) were conducted. Logistic regression was used to determine risk factors associated with ITN utilization. Results: The utilization of ITN was high (47%) for young women aged 15-24 years old. Overall, 67% of pregnant women aged 15-44 years old slept under bed nets the night prior the survey day. In the univariable analyses, being 35-44 years of age (OR 0.25; 95% CI: 0.07-0.89, p<0.02) and having information about malaria (OR 0.28, 95% CI: 0.09-0.85, p<0.03), were independently associated with ITN utilization. In the multivariate logistic regression model, none of the explanatory variables were significant at the 5% level. The study showed 98.8% overall coverage of ITNs among pregnant women in terms of possession. Conclusion: These findings have implications for malaria interventions in Namibia. While almost all the pregnant women recruited in the study possessed ITNs, a significant proportion did not utilize them. Older women were more likely to utilize ITNs. Interventions to improve utilization among pregnant women should target younger women below the age of 35. Women that had information on malaria were more likely to utilize ITN. Sensitising women about the epidemiology of malaria across Namibia could lead to improved utilization of ITNs. A national malaria strategic plan needs to incorporate targeted reproductive women’s education for malaria control in Namibia.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology and Biostatistics
Keywords: Pregnancy; Insecticide-Treated Bednets; Malaria